Pendidikan Agama Islam Di Sekolah Dasar Pengertian dan Ruang Lingkup - Ahmad Baydowi; Luigi Indar Alkhalani (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2024)
The Islamic Religious Education (PAI) curriculum in elementary schools has a strategic role in shaping students' character from an early age. This article discusses the definition, scope, and basic framework of the PAI curriculum implemented at the elementary level. The PAI curriculum is designed to instill the values of faith, noble character, and basic understanding of Islamic teachings in accordance with children's age development. The scope of the PAI curriculum includes aspects of belief, worship, morals, and Islamic history, which are delivered through an active and contextual learning approach. The basic framework of this curriculum is based on the national education goals and the vision of building a tolerant and broad-minded religious character. With a holistic approach, the PAI curriculum is expected to form students who not only understand religious teachings, but are also able to apply them in daily life. PAI learning in primary schools also emphasizes the development of students' spiritual and social competencies in order to be able to face moral challenges in the future. Through a structured and effective curriculum, religious education is expected to be a strong foundation in forming a generation with character, noble character, and harmonious national values.